2018
DOI: 10.1002/ps.5127
|View full text |Cite
|
Sign up to set email alerts
|

Paralogous Cyp51s mediate the differential sensitivity of Fusarium oxysporum to sterol demethylation inhibitors

Abstract: FoCYP51A and FoCYP51B are responsible for sensitivity to different azoles. These findings have direct implications for fungicide application strategies of plant and human diseases caused by F. oxysporum. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…The evolution of the gene families that contain genes involved in drug resistance might also give us clues on how drug resistance evolves in fungal populations; previous studies (Hawkins et al, 2014;Zheng et al, 2019) report two paralogs of cyp51 in diverse species, including A. fumigatus, A. nidulans, Penicillium digitatum, and Magnaporthe oryzae, while Fusarium graminearum, A. flavus, and A. oryzae have three cyp51 genes (Dudakova et al, 2017). Recently, a study proposed the existence of cyp51C gene arising from a duplication in cyp51B in A. terreus and A. carbonarius (Perez-Cantero et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of the gene families that contain genes involved in drug resistance might also give us clues on how drug resistance evolves in fungal populations; previous studies (Hawkins et al, 2014;Zheng et al, 2019) report two paralogs of cyp51 in diverse species, including A. fumigatus, A. nidulans, Penicillium digitatum, and Magnaporthe oryzae, while Fusarium graminearum, A. flavus, and A. oryzae have three cyp51 genes (Dudakova et al, 2017). Recently, a study proposed the existence of cyp51C gene arising from a duplication in cyp51B in A. terreus and A. carbonarius (Perez-Cantero et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Fusarium spp. also have three Cyp51 paralogues (Cyp51A, -B, and -C), with Cyp51C being unique to the genus [ 44 , 45 ]. However, Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergilli have two CYP51 orthologues (CYP51A and CYP51B) (Mellado et al, 2001) whereas Fusarium spp. have three CYP51 orthologues (CYP51A, CYP51B and CYP51C) (Becher et al, 2011;Zheng et al, 2019;James et al, 2020). The CYP51C orthologue is a unique characteristic of this fungal genus.…”
Section: Introductionmentioning
confidence: 99%
“…The CYP51C orthologue is a unique characteristic of this fungal genus. CYP51A and CYP51B are sterol 14-α demethylases, but the function of CYP51C remains unknown (Fan et al, 2013;Zheng et al, 2019). We have recently reported a 23 bp CYP51A promoter deletion that was associated with increased VRC resistance in both clinical and environmental FSSC isolates (James et al, 2020).…”
Section: Introductionmentioning
confidence: 99%